Model Analytical Development for Physical, Chemical, and Biological Characterization of Momordica charantia Vegetable Drug - Deysiane Oliveira Brandão; Geovani Pereira Guimarães; Ravely Lucena Santos; Fernando José de Lima Ramos Júnior; Karla Monik Alves da Silva; Fabio Santos de Souza; Rui Oliveira Macêdo (Journal of Analytical Methods in Chemistry)
Momordica charantia is a species cultivated throughout the world and widely used in folk medicine, and its medicinal benefits are well documented, especially its pharmacological properties, including antimicrobial activities. Analytical methods have been used to aid in the characterization of compounds derived from plant drug extracts and their products. This paper developed a methodological model to evaluate the integrity of the vegetable drug M. charantia in different particle sizes, using different analytical methods. M. charantia was collected in the semiarid region of Paraíba, Brazil. The herbal medicine raw material derived from the leaves and fruits in different particle sizes was analyzed using thermoanalytical techniques as thermogravimetry (TG) and differential thermal analysis (DTA), pyrolysis coupled to gas chromatography/mass spectrometry (PYR-GC/MS), and nuclear magnetic resonance (1H NMR), in addition to the determination of antimicrobial activity. The different particle surface area among the samples was differentiated by the techniques. DTA and TG were used for assessing thermal and kinetic parameters and PYR-GC/MS was used for degradation products chromatographic identification through the pyrograms. The infusions obtained from the fruit and leaves of Momordica charantia presented antimicrobial activity.